International study on nurses' views and experiences of compassion - Papadopoulos, Irena; Zorba, Akile; Koulouglioti, Christina; Ali, Sheila; Aagard, Magdeline; Akman, Ozlem; Alpers, Lise-Merete; Apostolara, Paraskevi; Biles, Jessica; Martín-García, Ángel; González-Gil, Teresa; Kouta, Christiana; et al. (My University, 2016)
Compassion is considered the cornerstone of nursing practice. However, the recent failures in delivering high-quality compassionate nursing care in the UK's National Health Service have brought the topic of compassion to the attention of the public, service providers, policy makers and academics.
Keywords: Compassion; Culture; International; Nurses’ Views; Nursing Online Survey; Quantitative